Electro-catalysis-based quasi-in-situ three-dimensional element analysis method
By combining electron energy loss spectrum and electron tomography technology, a three-dimensional reconstruction model was generated, which solved the problem of quasi-in-situ three-dimensional element analysis of electrocatalytic bases, and achieved accurate analysis of the electrocatalyst reaction process and in-depth study of element distribution.
Patent Information
- Application Number
- CN202411872396.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-04-04
AI Technical Summary
The prior art is difficult to realize the quasi-in-situ three-dimensional element analysis of electrocatalytic bases, especially in the in-depth study of the morphology structure of the electrocatalyst and the three-dimensional distribution of elements at different reaction stages.
The electron energy loss spectrum combined with electron tomography three-dimensional reconstruction technology is used to form a quasi-in-situ catalytic group by dropping catalyst on the loading network, and the electron energy loss spectrum images are collected at different reaction stages, and zero-peak correction, power-law model and Fourier deconvolution processing are performed, and the three-dimensional reconstruction model is finally generated for analysis.
Quasi-in-situ three-dimensional element analysis of electrocatalytic bases is realized, accurate sample information is obtained, element distribution is accurately analyzed, data processing is improved, and more comprehensive information is provided.
Smart Images

Figure CN119756980A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electrocatalysis research, in particular to a quasi-in-situ three-dimensional element analysis method of an electrocatalysis-based material. Background Art
[0002] There are many different kinds of electrocatalytic research, and the primary task is to design and prepare electrocatalysts with high activity, high selectivity and long life for specific reactions. After years of development, most of the catalysts used in the field of electrocatalysis are nanomaterials. How to obtain the three-dimensional element distribution at each stage of the reaction is crucial to understanding the physical and chemical properties of the material. Electron energy loss spectroscopy is a technique used to measure the change in kinetic energy after the interaction between electrons and samples. This technique is used to determine the atomic structure and type and chemical state of the elements of the sample. Currently, researchers widely use electron energy loss spectroscopy to study the two-dimensional element distribution and valence bond structure of materials. The use of electron energy loss spectroscopy for three-dimensional reconstruction research has not been widely used. There is no public quasi-in-situ three-dimensional elemental analysis method for electrocatalytic bases, and it is even more impossible to obtain the morphological structure and three-dimensional distribution of elements of electrocatalysts at different reaction stages. Summary of the invention
[0003] The present invention proposes an electrocatalytic-based quasi-in-situ three-dimensional elemental analysis method, which can realize quasi-in-situ sample preparation, obtain accurate sample information, and achieve precise analysis of element distribution.
[0004] The present invention adopts the following technical solutions.
[0005] A quasi-in-situ three-dimensional elemental analysis method for an electrocatalytic base, wherein a catalyst is dripped onto a carrier grid to form a quasi-in-situ catalytic base, and then the carrier grid is fixed at an electrode for reaction, so as to reduce the sample transfer steps and make the reaction scene closer to the actual use scene of the catalytic base. When analyzing the catalyst reaction process, the electron energy loss spectrum at different stages of the reaction process is combined with electron tomography three-dimensional reconstruction technology to generate a three-dimensional reconstruction model, and then the three-dimensional reconstruction models are superimposed, and the superimposed model data are analyzed.
[0006] The carrier grid is a copper carrier grid.
[0007] The copper grid is covered with a micro-grid film.
[0008] The method comprises the following steps: Step S1, taking a powdered nanocatalyst sample for electrocatalytic reaction and a mixed solution formed by naphthol and isopropanol, mixing them to prepare ink, and then ultrasonically treating the ink; Step S2, under the irradiation of an infrared baking lamp, use a pipette to absorb the same amount of the ink each time, take it out several times and drop it on the copper grid covered with the micro-grating film, wait for baking and drying; use tweezers to clamp the grid with the front side facing up and place it on the center of the electrode, use a leather ring with a hole in the center to cover the edge of the grid, and fix it on the electrode; Step S3, after assembling the electrode, the counter electrode and the reference electrode into a three-electrode system, placing the electrode in an electrochemical reaction cell and connecting the workstation; obtaining sample-carrying grids at different reaction stages by changing the magnitude of the applied voltage and the length of the polarization time for different grids; Step S4, transferring the grids carrying the samples at different reaction stages to a high-tilt-angle transmission electron microscope three-dimensional reconstruction sample rod, using the transmission electron microscope, rotating the sample rod in a scanning transmission mode, and collecting electron energy loss spectrum electron tomography images of the grids carrying the samples at different angles; Step S5, performing zero peak correction on the obtained series of electron energy loss spectra, using a power law model method to deduct the influence of the background, and using a Fourier deconvolution method to remove the multiple scattering influence caused by thickness, and finally obtaining a series of two-dimensional element distribution images of different elements; Step S6: manually align the images, then use the synchronous iterative reconstruction technology to generate a 3D reconstructed model, and then perform rendering and 3D result analysis.
[0009] In step S1, the amount of the powdered nanocatalyst is 2 mg, the amount of the mixed solution is 1 ml, the mixed solution is formed by mixing naphthol and isopropanol in a ratio of 1:39, and the ultrasonic treatment time of the ink is 30 minutes.
[0010] In step S2, 2.5 ul of the ink is sucked up each time using a pipette, and the ink is taken four times and dropped onto the grid. The electrode is an L-shaped glassy carbon electrode with a diameter of 3 mm.
[0011] In step S6, the images are manually aligned using Tomviz software.
[0012] The catalyst is an Ag@Cu20 core-shell structure nanomaterial for Co2RR electrocatalysis; In step S6, the two-dimensional projection images of the grid carrying the sample acquired from different rotation angles are accurately aligned into a continuous tilt sequence by manual alignment.
[0013] Step S6 is for the Ag@Cu20 core-shell structure nanomaterial sample used for Co2RR electrocatalysis. The manual alignment method is as follows: in step S5, there is a missing circular area in the two-dimensional images of the O element and the Cu element obtained after processing the electron energy loss spectrum electron tomography image collected, and there is a bright circular area in the center of the collected ADF image. This area is the location of the Ag element, which is set as a characteristic structure. By adjusting the position of each image by translation in the x and y directions, the missing circular characteristic area is aligned to complete the image alignment operation. The specific operation is to overlap the two-dimensional projection images of the sample at the front and back angles in sequence for visualization (such as the first and second images, the second and third images...), by identifying the characteristic points or characteristic structures in the sample, and moving the image along the x and y directions, the front and back images at different inclination angles match these characteristic points or characteristic structures, and finally each image is aligned, so that the aligned series of two-dimensional projection images have a high degree of overlap, that is, the features of the same area are in the same position in different images; and the image shows continuity after alignment without obvious offset.
[0014] Step S6: For the Ag@Cu20 core-shell structure nanomaterial sample used for Co2RR electrocatalysis, the method of using the synchronous iterative reconstruction technology to generate a three-dimensional reconstruction model is as follows: first, the two-dimensional tilt sequence of the O element after manual alignment is input, the corresponding rotation acquisition angle of each two-dimensional image during acquisition is input, and then the number of iterations is input 100 times. The synchronous iterative reconstruction technology continuously optimizes the estimation of the three-dimensional density distribution by performing projection simulation and back-projection to update the density distribution, and finally obtains an accurate three-dimensional reconstruction result of the O element; the regions where different elements are located are color rendered separately, the three-dimensional structures of O and Cu are superimposed together, and the three-dimensional reconstruction results of the four different reaction stages are analyzed, such as Figure 2 As shown; In step S6, the two-dimensional elemental maps of O and Cu at the same angle in the same reaction stage are simultaneously extracted by collecting the same EELS spectrum, so that the movement sizes of O and Cu at the same angle in the same stage in the x and y directions are the same during manual alignment, and further the relative positions of O and Cu elements in the three-dimensional space are the same after three-dimensional reconstruction, so that the three-dimensional structures of O and Cu at the same reaction stage can be superimposed together.
[0015] The advantages of the present invention are: 1. Quasi-in-situ sample preparation: by controlling different applied voltages, grids at different reaction stages can be obtained at the same time, which can obtain more accurate sample information and achieve precise analysis of element distribution.
[0016] 2. The electron energy loss spectrum is processed using methods such as zero-peak correction, power-law model and Fourier deconvolution, and an accurate two-dimensional element distribution image can be obtained, which improves the accuracy and reliability of data processing.
[0017] 3. Electron energy loss spectrum combined with three-dimensional reconstruction technology can conduct in-depth exploration and analysis of element distribution and provide more comprehensive information.
[0018] 4. Using the mainstream 3D reconstruction software Tomviz for manual alignment and synchronous iterative reconstruction technology, high-quality 3D reconstruction models can be generated, providing a reliable basis for further rendering and result analysis.
[0019] The present invention can be used in the following fields: 1. Quasi-in-situ sample preparation: The samples obtained using this method can not only be used for transmission electron microscopy characterization, but also for other chemical tests.
[0020] 2. Catalyst research: It can be used for the research and development of various electrocatalytic materials. Through three-dimensional reconstruction and element distribution, it can deeply understand the material structure and performance, and analyze catalyst samples at different reaction stages.
[0021] 3. Nanotechnology: used for the research and application of nanomaterials, exploring the characteristics and functions of nanostructures through electron microscopy and energy loss spectroscopy analysis.
[0022] The present invention is implemented through the above steps and techniques, has broad application prospects, can play an important role in multiple fields, and bring new possibilities and development opportunities for research and application in related fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] The present invention is further described in detail below with reference to the accompanying drawings and specific embodiments: Attached Figure 1 It is a schematic diagram of the process of the present invention; Attached Figure 2 3D reconstruction is a schematic diagram of an embodiment of the present invention. DETAILED DESCRIPTION
[0024] As shown in the figure, a quasi-in-situ three-dimensional elemental analysis method for an electrocatalytic base is provided. In the method, a catalyst is dripped onto a carrier grid to form a quasi-in-situ catalytic base, and the carrier grid is then fixed at an electrode for reaction, so as to reduce the sample transfer steps and make the reaction scenario closer to the actual use scenario of the catalytic base. When analyzing the catalyst reaction process, the electron energy loss spectrum at different stages of the reaction process is combined with electron tomography three-dimensional reconstruction technology to generate a three-dimensional reconstruction model, and then the three-dimensional reconstruction models are superimposed, and the superimposed model data is analyzed.
[0025] The carrier grid is a copper carrier grid.
[0026] The copper grid is covered with a micro-grid film.
[0027] The method comprises the following steps: Step S1, taking a powdered nanocatalyst sample for electrocatalytic reaction and a mixed solution formed by naphthol and isopropanol, mixing them to prepare ink, and then ultrasonically treating the ink; Step S2, under the irradiation of an infrared baking lamp, use a pipette to absorb the same amount of the ink each time, take it out several times and drop it on the copper grid covered with the micro-grating film, wait for baking and drying; use tweezers to clamp the grid with the front side facing up and place it on the center of the electrode, use a leather ring with a hole in the center to cover the edge of the grid, and fix it on the electrode; Step S3, after assembling the electrode, the counter electrode and the reference electrode into a three-electrode system, placing the electrode in an electrochemical reaction cell and connecting the workstation; obtaining sample-carrying grids at different reaction stages by changing the magnitude of the applied voltage and the length of the polarization time for different grids; Step S4, transferring the grids carrying the samples at different reaction stages to a high-tilt-angle transmission electron microscope three-dimensional reconstruction sample rod, using the transmission electron microscope, rotating the sample rod in a scanning transmission mode, and collecting electron energy loss spectrum electron tomography images of the grids carrying the samples at different angles; Step S5, performing zero peak correction on the obtained series of electron energy loss spectra, using a power law model method to deduct the influence of the background, and using a Fourier deconvolution method to remove the multiple scattering influence caused by thickness, and finally obtaining a series of two-dimensional element distribution images of different elements; Step S6: manually align the images, then use the synchronous iterative reconstruction technology to generate a 3D reconstructed model, and then perform rendering and 3D result analysis.
[0028] In step S1, the amount of the powdered nanocatalyst is 2 mg, the amount of the mixed solution is 1 ml, the mixed solution is formed by mixing naphthol and isopropanol in a ratio of 1:39, and the ultrasonic treatment time of the ink is 30 minutes.
[0029] In step S2, 2.5 ul of the ink is sucked up each time using a pipette, and the ink is taken four times and dropped onto the grid. The electrode is an L-shaped glassy carbon electrode with a diameter of 3 mm.
[0030] In step S6, the images are manually aligned using Tomviz software.
[0031] The catalyst is an Ag@Cu20 core-shell structure nanomaterial for Co2RR electrocatalysis; In step S6, the two-dimensional projection images of the grid carrying the sample acquired from different rotation angles are accurately aligned into a continuous tilt sequence by manual alignment.
[0032] Step S6 is for the Ag@Cu20 core-shell structure nanomaterial sample used for Co2RR electrocatalysis. The manual alignment method is as follows: in step S5, there is a missing circular area in the two-dimensional images of the O element and the Cu element obtained after processing the electron energy loss spectrum electron tomography image collected, and there is a bright circular area in the center of the collected ADF image. This area is the location of the Ag element, which is set as a characteristic structure. By adjusting the position of each image by translation in the x and y directions, the missing circular characteristic area is aligned to complete the image alignment operation. The specific operation is to overlap the two-dimensional projection images of the sample at the front and back angles in sequence for visualization (such as the first and second images, the second and third images...), by identifying the characteristic points or characteristic structures in the sample, and moving the image along the x and y directions, the front and back images at different inclination angles match these characteristic points or characteristic structures, and finally each image is aligned, so that the aligned series of two-dimensional projection images have a high degree of overlap, that is, the features of the same area are in the same position in different images; and the image shows continuity after alignment without obvious offset.
[0033] Step S6: For the Ag@Cu20 core-shell structure nanomaterial sample used for Co2RR electrocatalysis, the method of using the synchronous iterative reconstruction technology to generate a three-dimensional reconstruction model is as follows: first, the two-dimensional tilt sequence of the O element after manual alignment is input, the corresponding rotation acquisition angle of each two-dimensional image during acquisition is input, and then the number of iterations is input 100 times. The synchronous iterative reconstruction technology continuously optimizes the estimation of the three-dimensional density distribution by performing projection simulation and back-projection to update the density distribution, and finally obtains an accurate three-dimensional reconstruction result of the O element; the regions where different elements are located are color rendered separately, the three-dimensional structures of O and Cu are superimposed together, and the three-dimensional reconstruction results of the four different reaction stages are analyzed, such as Figure 2 As shown; In step S6, the two-dimensional elemental maps of O and Cu at the same angle in the same reaction stage are simultaneously extracted by collecting the same EELS spectrum, so that the movement sizes of O and Cu at the same angle in the same stage in the x and y directions are the same during manual alignment, and further the relative positions of O and Cu elements in the three-dimensional space are the same after three-dimensional reconstruction, so that the three-dimensional structures of O and Cu at the same reaction stage can be superimposed together.
[0034] Example: like Figure 2 As shown, in this example, the Cu and O elements in the Ag@Cu2O nanocore-shell material used for the Co2RR reaction were extracted for quasi-in-situ three-dimensional elemental analysis, as follows: 1. Prepare ink by mixing 2 mg of Ag@Cu20 core-shell structured nanomaterials for Co2RR electrocatalysis with 1 ml of a mixed solution of naphthol and polypropanol (1:39), and then ultrasonicate for 30 minutes.
[0035] 2. Under the irradiation of infrared baking lamp, use a pipette to absorb 2.5ul of this ink, drop it four times on the copper grid covered with micro-corona film, and wait for baking and drying. Clamp the grid with tweezers, place it face up on the center of the L-shaped glassy carbon electrode with a diameter of 3mm, and use a leather ring with a central hole to cover the edge of the grid and fix it on the L-shaped glassy carbon electrode.
[0036] 3. Assemble the glassy carbon electrode, the counter electrode and the reference electrode into a three-electrode system, where the counter electrode is a platinum counter electrode, the reference electrode is an Ag / AgCl reference electrode, the electrolyte is 0.1 M KHCO3, and an H-type electrolytic cell is used. Connect the workstation and prepare four samples in sequence. Apply voltages of 0V, -0.7V, -1.2V, and -1.4V vs RHE, respectively. The polarization time is 600s. After the reaction, carefully remove the grid and gently rinse it with ethanol solution, and then use an infrared baking lamp to bake and dry it, and you can get the grid with samples at different reaction stages.
[0037] 4. The grids carrying samples at the above different reaction stages were transferred to the high-tilt-angle transmission electron microscope three-dimensional reconstruction sample rod in sequence. The transmission electron microscope was used to rotate the sample rod in the scanning transmission mode to collect electron energy loss spectrum electron tomography images at different angles. The acquisition parameters were set as follows: Dispersion was set to 0.3ev / channel, the acquisition time for each pixel was 0.1s, and the Highloss range of the collected EELS spectrum was 470ev-1064ev, including the information of O k-edge (532ev) and Cu L-edge (931ev).
[0038] 5. The obtained series of electron energy loss spectra were subjected to zero peak correction, the background effect was deducted using the power law model method, and the multiple scattering effect caused by thickness was removed using the Fourier deconvolution method, and finally a series of two-dimensional element distribution images of Cu and O elements were obtained.
[0039] 6. Use Tomviz software to manually align the images, and then use the synchronous iterative reconstruction technology to iterate 100 times to generate a 3D reconstruction model, and then perform color rendering. Finally, the results of Cu and O are superimposed, and the 3D reconstruction results of the four different reaction stages are analyzed in 3D. From the results, it can be seen that as the reaction proceeds, Cu is evenly distributed on the particles, and the O element is partially digested near the surface and inside.
Claims
1. A quasi-in-situ three-dimensional elemental analysis method based on electrocatalysis, characterized in that: In the method, the catalyst is dripped onto the carrier grid to form a quasi-in-situ catalytic base, and then the carrier grid is fixed at the electrode for reaction, so as to reduce the sample transfer steps and make the reaction scene closer to the actual use scene of the catalytic base. When analyzing the catalyst reaction process, the electron energy loss spectrum at different stages of the reaction process is combined with the electron tomography three-dimensional reconstruction technology to generate a three-dimensional reconstruction model, and then the three-dimensional reconstruction models are superimposed, and the superimposed model data is analyzed.
2. The electrocatalytic quasi-in-situ three-dimensional elemental analysis method according to claim 1, characterized in that: The carrier grid is a copper carrier grid.
3. The electrocatalytic quasi-in-situ three-dimensional elemental analysis method according to claim 2, characterized in that: The copper grid is covered with a micro-grid film.
4. The electrocatalytic quasi-in-situ three-dimensional elemental analysis method according to claim 3, characterized in that: The method comprises the following steps: Step S1, taking a powdered nanocatalyst sample for electrocatalytic reaction and a mixed solution formed by naphthol and isopropanol, mixing them to prepare ink, and then ultrasonically treating the ink; Step S2, under the irradiation of an infrared baking lamp, use a pipette to absorb the same amount of the ink each time, take it out several times and drop it on the copper grid covered with the micro-grating film, wait for baking and drying; use tweezers to clamp the grid with the front side facing up and place it on the center of the electrode, use a leather ring with a hole in the center to cover the edge of the grid, and fix it on the electrode; Step S3, after assembling the electrode, the counter electrode and the reference electrode into a three-electrode system, placing the electrode in an electrochemical reaction cell and connecting the workstation; obtaining sample-carrying grids at different reaction stages by changing the magnitude of the applied voltage and the length of the polarization time for different grids; Step S4, transferring the grids carrying the samples at different reaction stages to a high-tilt-angle transmission electron microscope three-dimensional reconstruction sample rod, using the transmission electron microscope, rotating the sample rod in a scanning transmission mode, and collecting electron energy loss spectrum electron tomography images of the grids carrying the samples at different angles; Step S5, performing zero peak correction on the obtained series of electron energy loss spectra, using a power law model method to deduct the influence of the background, and using a Fourier deconvolution method to remove the multiple scattering influence caused by thickness, and finally obtaining a series of two-dimensional element distribution images of different elements; Step S6: manually align the images, then use the synchronous iterative reconstruction technology to generate a 3D reconstructed model, and then perform rendering and 3D result analysis.
5. The electrocatalytic quasi-in-situ three-dimensional elemental analysis method according to claim 4, characterized in that: In step S1, the amount of the powdered nanocatalyst is 2 mg, the amount of the mixed solution is 1 ml, the mixed solution is formed by mixing naphthol and isopropanol in a ratio of 1:39, and the ultrasonic treatment time of the ink is 30 minutes.
6. The electrocatalytic quasi-in-situ three-dimensional elemental analysis method according to claim 4, characterized in that: In step S2, 2.5 ul of the ink is sucked up each time using a pipette, and the ink is taken four times and dropped onto the grid. The electrode is an L-shaped glassy carbon electrode with a diameter of 3 mm.
7. The electrocatalytic quasi-in-situ three-dimensional elemental analysis method according to claim 4, characterized in that: In step S6, the images are manually aligned using Tomviz software.
8. The electrocatalytic quasi-in-situ three-dimensional elemental analysis method according to claim 7, characterized in that: The catalyst is an Ag@Cu20 core-shell structure nanomaterial for Co2RR electrocatalysis; In step S6, the two-dimensional projection images of the grid carrying the sample acquired from different rotation angles are accurately aligned into a continuous tilt sequence by manual alignment.
9. The electrocatalytic quasi-in-situ three-dimensional elemental analysis method according to claim 8, characterized in that: Step S6: For the Ag@Cu20 core-shell structure nanomaterial sample used for Co2RR electrocatalysis, the manual alignment method is as follows: in step S5, there is a missing circular area in the two-dimensional images of the O element and the Cu element obtained after processing the electron energy loss spectrum electron tomography image collected, and there is a bright circular area in the center of the collected ADF image, which is the location of the Ag element, and it is set as a characteristic structure. By adjusting the position of each image by translation in the x and y directions, the missing circular characteristic area is aligned to complete the image alignment operation. The specific operation is to overlap the two-dimensional projection images of the sample at the front and back angles in sequence for visualization, and by identifying the characteristic points or characteristic structures in the sample and moving the image along the x and y directions, the front and back images at different tilt angles are matched with these characteristic points or characteristic structures. Finally, each image is aligned, so that the aligned series of two-dimensional projection images have a high degree of overlap, that is, the features of the same area are consistent in position in different images; And the images show continuity after alignment without obvious offset.
10. The electrocatalytic-based quasi-in-situ three-dimensional elemental analysis method according to claim 9, characterized in that: Step S6: For the Ag@Cu20 core-shell structure nanomaterial sample used for Co2RR electrocatalysis, the method of using the synchronous iterative reconstruction technology to generate a three-dimensional reconstruction model is as follows: first, input the manually aligned two-dimensional tilt sequence of the O element, input the corresponding rotation acquisition angle of each two-dimensional image during acquisition, and then input the number of iterations 100 times. The synchronous iterative reconstruction technology continuously optimizes the estimation of the three-dimensional density distribution by performing projection simulation and back-projection to update the density distribution, and finally obtains an accurate three-dimensional reconstruction result of the O element; color rendering is performed on the regions where different elements are located, the three-dimensional structures of O and Cu are superimposed together, and the three-dimensional reconstruction results of the four different reaction stages are analyzed; In step S6, the two-dimensional elemental maps of O and Cu at the same angle in the same reaction stage are simultaneously extracted by collecting the same EELS spectrum, so that the movement sizes of O and Cu at the same angle in the same stage in the x and y directions are the same during manual alignment, and further the relative positions of O and Cu elements in the three-dimensional space are the same after three-dimensional reconstruction, so that the three-dimensional structures of O and Cu at the same reaction stage can be superimposed together.
Citation Information
Patent Citations
Device and method for research on liquid-phase catalysis system heterogeneous catalyst same position microstructural evolution
CN109142615A
Transmission electron microscope technology for in-situ study of three-dimensional distribution structure of nanoparticles
CN110208168A
In-situ analysis method for morphology and three-dimensional structure of platinum-copper alloy nano-catalyst
CN111505030A
Electrochemical electrode three-dimensional morphology in-situ characterization method based on CT (Computed Tomography) technology
CN112858413A
High-temperature electrochemical system electrode interface 3D morphology characterization method based on CT technology
CN112964739A